If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = 5x + -10 Reorder the terms: 3(4 + x) = 5x + -10 (4 * 3 + x * 3) = 5x + -10 (12 + 3x) = 5x + -10 Reorder the terms: 12 + 3x = -10 + 5x Solving 12 + 3x = -10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 12 + 3x + -5x = -10 + 5x + -5x Combine like terms: 3x + -5x = -2x 12 + -2x = -10 + 5x + -5x Combine like terms: 5x + -5x = 0 12 + -2x = -10 + 0 12 + -2x = -10 Add '-12' to each side of the equation. 12 + -12 + -2x = -10 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -10 + -12 -2x = -10 + -12 Combine like terms: -10 + -12 = -22 -2x = -22 Divide each side by '-2'. x = 11 Simplifying x = 11
| 8y^2=-9y+4 | | 10x-7=29-14x | | 81t^2+144t+64= | | 10-7x=29-14xr | | 3y-1+y+47=7y+50-5y | | 7x-11=2x+14 | | 17x+19y=-23 | | 19x+17y=-23 | | -17-10=7x+17 | | 7x-22=41 | | 5*12+10=4*12+p | | 5*-12+10=4*-12+p | | 5-12+10=4*-12+p | | 83=32x+10 | | 18-12+2+1= | | 60-4x=32x+16 | | 8x+4=6x+10 | | -19.48+x=28.03 | | 3x+8=-8-7x | | 10-3h=25 | | y=-4x+0 | | 5t+1=11 | | 82-5x=22x+16 | | 4x-9=175 | | 11-7x=19-14x | | 6m+11=137 | | 9y-47=43 | | 2y=36 | | b+5=59 | | 9b+24=150 | | 3x-21=1479 | | x^3+x^2-8x-12=0 |